Polymer nanofiber formed particle, preparation method thereof and lithium battery diaphragm coating slurry comprising polymer nanofiber formed particle
By preparing polymer nanofiber molded particles and compounding them with inorganic nanopowders to form composite particles with core-shell structures or beaded structures, the problems of high viscosity and low solid content of nanofibers in the lithium battery separator coating are solved, high heat resistance, puncture strength and electrolyte wetting are achieved, and the safety and performance of the battery are enhanced.
Patent Information
- Application Number
- CN202411742427.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-25
AI Technical Summary
The high viscosity and low solids content of polymer nanofibers in the existing lithium battery separator coating lead to poor coating effect, and the nanofibers are prone to agglomeration, affecting battery performance and safety.
By preparing polymer nanofiber molded particles and compounding them with inorganic nanopowders to form composite particles with core-shell structures or beaded structures, they are used to prepare lithium battery separator coating slurry. The method includes stirring, homogeneous emulsification, low-temperature drying, heating crystallization, sieving and demagnetization treatment to form a stable and highly solid coating slurry.
The high heat resistance, puncture strength and electrolyte wetting of the lithium battery separator coating are achieved, the viscosity is reduced, the solid content is improved, the problem of nanofiber agglomeration is solved, and the safety and performance of the battery is enhanced.
Smart Images

Figure BDA0005162855100000111 
Figure BDA0005162855100000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium batteries, and in particular to polymer nanofiber formed particles, a preparation method thereof, and a lithium battery diaphragm coating slurry comprising the same. Background Art
[0002] Lithium-ion batteries have been widely used in 3C consumer products, energy storage and power, and have also been used in some special scenarios such as drones, aircraft, cranes, freight, etc. With the expansion of various application scenarios, special application scenarios have higher requirements for battery performance and safety.
[0003] The battery separator is a key component of the battery. It is located between the positive electrode and the negative electrode to prevent the positive and negative electrodes from contacting and short-circuiting. At the same time, the micropores on the separator allow lithium ions to pass through, thereby generating current. The performance of the separator directly affects the battery's capacity, cycle performance, safety performance and other characteristics. Batteries have higher and higher requirements for separator materials, but porous base membranes based on polyolefins are still irreplaceable, and some new materials are increasingly used in coatings.
[0004] Cellulose nanofiber whiskers (CNC), cellulose nanofibers (CNF), aramid nanofibers, PI nanofibers, PAN nanofibers, PAM nanofibers, PVDF nanofibers, PPS nanofibers, PEEK nanofibers and other polymer fiber materials have various excellent material properties such as ultra-high specific surface area, hydrophilicity and lipophilicity, high temperature resistance, high strength, high modulus, etc. Theoretically, they are excellent coating materials for secondary battery separator coatings. However, when such materials are dispersed or dissolved in solvents, the viscosity of the coating system will be greatly increased. Therefore, in order to ensure the normal coating effect, whether it is a water-based system or an oil-based system, the addition amount is only within 5%, or even within 1%, and the slurry viscosity is extremely high.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a polymer nanofiber shaped particle and a preparation method thereof and a lithium battery separator coating slurry comprising the same, so as to solve the above problems.
[0007] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:
[0008] A method for preparing polymer nanofiber shaped particles, the method comprising: preparing one or more polymer nanofibers into a dispersion, stirring at a speed of 1000-1200 r / min and then homogenizing and emulsifying, and then sequentially performing low-temperature drying, heating crystallization, crushing and screening, and demagnetization treatment to obtain the polymer nanofiber shaped particles;
[0009] The polymer nanofibers include any one or more of cellulose nanofiber whiskers (CNC), cellulose nanofibers (CNF), aramid nanofibers, PI nanofibers, PAN nanofibers, PAM nanofibers, PVDF nanofibers, PPS nanofibers, and PEEK nanofibers;
[0010] The viscosity of the dispersion is less than 500 cp.
[0011] Preferably, the screening is performed using a 100-400 mesh screen; the particle size of cellulose is generally 4-10 nm, the particle size of PI fiber is 0.3-0.7 um, and the particle size of the obtained polymer nanofiber formed particles is 0.2-1 um.
[0012] Optionally, the temperature of the low-temperature drying is 60-90°C; preferably, the temperature of the low-temperature drying is 60-70°C.
[0013] Optionally, the heating temperature is set to be 10-40° C. lower than the melting point of the polymer nanofiber material; preferably, the heating time is 24 hours.
[0014] Preferably, the preparation method further comprises: after the homogenization and emulsification, the emulsified product is subjected to vacuum freeze drying; preferably, the vacuum freeze drying comprises: firstly, rapid freezing at a temperature of -50°C to -55°C to form solid ice, and then vacuuming to a pressure of 5-10Pa and maintaining for 18 hours. The freeze drying process must be carried out in a vacuum environment to prevent the nanofibers from oxidizing and deteriorating, which helps to maintain their microstructure.
[0015] Preferably, the preparation method further comprises: adding inorganic nanopowder to the dispersion under stirring conditions, and continuously stirring for 60 minutes; preferably, the inorganic nanopowder comprises any one or more of α-phase alumina, γ-phase alumina, β-phase alumina, mixed-phase alumina, boehmite, silicon oxide, zirconium oxide, magnesium hydroxide, aluminum hydroxide, aluminum titanate, barium titanate, lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum titanium oxide, sulfide electrolyte powder, lithium iron phosphate, lithium iron manganese phosphate, NCA ternary positive electrode, NCM ternary positive electrode, nano-silicon, micro-silicon, silicon-containing negative electrode material, and silicon-carbon negative electrode material.
[0016] The particle size of the inorganic nanopowder is 1nm-5000nm; preferably, the particle size of the inorganic nanopowder is 10nm-2000nm.
[0017] The polymer nanofiber forming particles provided by the invention are prepared by the preparation method.
[0018] The present invention also provides a lithium battery separator coating slurry, and the preparation method thereof comprises:
[0019] S1: mixing the polymer nanofiber forming particles prepared in the present invention, an aqueous dispersant and pure water to obtain a dispersion slurry, wherein the mass percentages of the polymer nanofiber forming particles, the aqueous dispersant and the pure water in the dispersion slurry are 5%-50%, 0.5%-5% and 50%-95% respectively;
[0020] S2: uniformly mixing the dispersed slurry obtained in S1 with the anti-settling agent aqueous solution, grinding, and obtaining a grinding slurry, wherein the mass percentage of the dispersed slurry in the grinding slurry is 10%-100%;
[0021] S3: mixing the grinding slurry obtained in S2, the binder and the wetting agent to obtain the lithium battery separator coating slurry;
[0022] The mass percentage of the grinding slurry in the coating slurry is 80%-97%, the mass percentage of the adhesive is 3%-20%, and the mass percentage of the wetting agent is 0.05%-4%.
[0023] The dispersant is selected from one or more of polycarboxylic acid ammonium salt, polycarboxylic acid sodium salt, polyacrylate, and phosphate ester;
[0024] The anti-settling agent is selected from one or more of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, cellulose, PVP, polyurethane block copolymers, polyacrylate copolymers, and polyvinyl pyrrolidone;
[0025] The adhesive is selected from one or more of an emulsion-type acrylate-based polymer, a solution-type acrylate-based polymer, a polyurethane polymer, a polyacrylamide polymer, a polyimide polymer, and a polyamide polymer;
[0026] The wetting agent is selected from one or more of an organosilicon-modified wetting agent, a polyether wetting agent, an acetylene alcohol wetting agent, and an alcohol wetting agent.
[0027] Preferably, the preparation method further comprises: hydrophobic modification of the dispersed slurry; the hydrophobic modification comprises: in the S2 step, adding a hydrophobic agent and mixing evenly before grinding, and then performing subsequent steps; preferably, the mass percentage of the hydrophobic agent in the grinding slurry is 1-10%.
[0028] The present invention uses a method of preparing a liquid dispersion into solid microspheres by heating and crystallizing, which "passivates" the active hydroxyl groups of cellulose, weakens the hydrogen bonding effect between molecules, increases the fluidity of the polymer chain, and reduces the macroscopic viscosity. The prior art generally uses polymer nanofibers in the form of fiber pulp. The present invention converts gel-state pulp into solid microparticles for application. The stability and crystallinity of the formed microparticles formed by special process adjustment are higher than those of the original pulp material, and are not limited by the viscosity of the pulp itself, so that a high-solid content, low-viscosity coating slurry can be achieved. This type of formed microparticle is added to the diaphragm coating or the positive and negative electrode slurry to improve the wettability of the electrolyte and quickly inject the liquid. At the same time, the material can bind free metal ions, trace water molecules, H-containing and fluorine-containing byproducts in the system, reduce the occurrence of side reactions in the battery system, and further prevent thermal runaway.
[0029] The present invention uses cellulose with a small aspect ratio (length 0.1-0.5um) and ultra-small particle size inorganic nanopowder (particle size 0.3um) to form a core-shell structure with inorganic nanopowder as the crystal core and short fibers as the shell through a secondary crystallization method. The formation of this structure has the following key advantages: First, by utilizing the adhesiveness of the polymer nanofibers themselves, the step of adding an adhesive can be eliminated when using the prepared core-shell structure composite material to configure the slurry. The polymer nanofibers wrapped in the shell can exert their own adhesiveness without the need for external adhesives, thereby ensuring the simplicity of the slurry system and the simplification of the coating process; second, the polymer nanofibers wrapped in the shell replace the traditional ceramic coating on the surface of the base film, solving the problems of poor wettability and low liquid absorption rate of traditional batteries; third, the polymer nanofibers are more insulating than inorganic materials, making the coating film resistant to high breakdown voltage; fourth, the polymer nanofibers wrapped in the inorganic nanopowder are cross-linked into a network structure to make the inorganic nanopowders more densely arranged, which not only improves the heat resistance of the coating but also improves the puncture strength, greatly ensuring the safety of the battery. The premise for forming the core-shell structure is that the ratio of polymer nanofibers to inorganic nanopowders needs to be strictly controlled. If too little cellulose is added, the core-shell structure cannot be effectively coated and the maximum advantage of this structure cannot be brought into play. If too much inorganic nanopowder is added, a large amount of ceramic surface will be exposed or even a reverse core-shell structure (cellulose wrapped by inorganic nanopowder) will be formed, which will lose the above advantages.
[0030] In addition, the method provided by the present invention compounds polymer nanofibers with inorganic materials to form secondary particles with a beaded structure. Polymer nanofibers with a high aspect ratio (length 1-3um) are compounded with ultra-small inorganic nanopowders (particle size 0.3um) to prepare a beaded structure with a "mutton skewers" shape, and a network structure formed by cross-linking the beaded structure. This improves the high heat resistance, high puncture resistance, high wettability, etc. of the coating film under low-thickness coating.
[0031] Based on the synthesis principle of beads, when the polymer solution is flowing and stirred under the action of shear stress, it is easy to crystallize and form beads with a "kebab" structure. Therefore, there are three key factors in preparing this structure: the first is the shear frequency of homogenization and emulsification. The preferred speed of the present application is 12000rpm and the power is 1100W. The high-frequency shear homogenization and emulsification of the homogenizer is used instead of the traditional stirring to weaken the hydrogen bonding between the fiber molecules. The nano-scale inorganic particles are proportional to the fiber molecules through the intermolecular force to form a "kebab" shape, but the structure is unstable at this time; the second is low-temperature freeze-drying. The product obtained by high-speed stirring of the homogenizer needs to be dehydrated by freeze-drying. Water maintains the morphology of the product. After dehydration, the inorganic nanopowders are bound to the fibers one by one. However, this is a physical effect and is still not stable enough (adding water and stirring will separate the two again). Direct heating and dehydration will destroy the intermolecular hydrogen bonds. Third, the freeze-dried product is heated and crystallized in an oven to strengthen the binding force between the fiber and the inorganic material. The temperature cannot be too low, otherwise the polymer chain will be difficult to straighten. The temperature cannot be too high, otherwise it will destroy the effect between the fiber and the inorganic material. The temperature is set to 10-40°C lower than the melting point of the nanofiber material. Different beads begin to cross-link and eventually form a mesh structure, and the nodes of the mesh are covered by the inorganic material bound on it. The mesh structure formed by the cross-linking of the bead structure provides more support sites for the base film, effectively improving the excellent properties of the coating film under the low coating, such as heat resistance and puncture resistance.
[0032] The composite coating that forms a network structure has certain requirements for the ratio of inorganic materials to polymer nanofibers: if the fiber mass fraction is too low, it is difficult to form enough beads and achieve effective cross-linking; if the inorganic material mass fraction is too low, it is difficult to form enough inorganic material attachment points, resulting in the exposure of network cellulose, which affects the coating performance, and too few active sites lead to secondary bonding of nanofibers due to their own hydrogen bonding. Therefore, there are high requirements for the ratio of the two formulas.
[0033] The polymer nanofiber shaped particles and preparation method provided by the present invention can be used not only for preparing coating slurries for coating lithium battery separators, but also for composite coating of NCM, NCA ternary materials, oxide electrolyte materials, and sulfide electrolyte materials. By forming particles with a composite structure, the resistance of NCM, NCA ternary materials, oxide electrolyte materials, and sulfide electrolyte materials to the external environment can be improved, the service life can be extended, the environmental requirements can be reduced, and the material function can be guaranteed; at the same time, it can also be applied to the composite coating of silicon-containing negative electrode materials. The process of particle molding after composite can restrain the silicon negative electrode particles, buffer the expansion of the silicon material during the charge and discharge process, and extend the service life of the silicon negative electrode material.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] When the polymer fiber material is added in a very small amount, the viscosity of the dispersion system or the dissolution system will increase dramatically, resulting in a very small amount of such material added to the coating slurry during actual application, and the coating cannot give full play to the performance advantages of such material itself. In addition, due to the extremely high intermolecular forces in the system, the nanofiber will continue to self-aggregate during the entire process of dispersion, circulation, coating, and drying. This is not a problem that can be solved by a simple chemical or physical dispersion system, and will lead to a series of problems such as uneven coating and particle agglomeration due to the self-aggregation of the nanofibers. The present invention prepares nanofibers into nano-molded particles alone or after compounding, or pre-compounds with nano-inorganic powders to form nano-molded particles with a core-shell structure, and coats them on the diaphragm, which can give full play to the various performance advantages of polymer nanofiber materials, and the shaped particles can be simply coated with water, and conventional coating equipment can be directly used, solving the difficult problem of the application of polymer nanofiber materials.
[0036] The polymer nanofiber shaped particles provided by the present invention can be applied under existing coating equipment and process schemes, solving the problems of easy agglomeration of polymer nanofibers, low solid content of pulp, high viscosity, and difficulty in use, and can realize a large-scale application mode of polymer nanofibers. The solid content of the polymer nanofibers in the slurry of the present invention can be increased to 20% at most, and the overall viscosity of the slurry can be controlled within 600cp. The solid content of conventional polymer nanofiber pulp is between 0.1-5%, and the pulp with more than 3% is jelly-like, and the pulp viscosity is above 5000cp, which cannot be directly coated.
[0037] The present invention can give full play to the material advantages of polymer nanofibers with high specific surface area and high strength, and realize the application value of the material. The slurry infiltration speed of the slurry-coated nanofiber coating diaphragm provided by the present invention is more than 5 times that of the ceramic coating diaphragm with the same thickness, and the puncture strength of the diaphragm coated with the nanofiber coating is increased by 10-50gf / um; at the same time, because the adhesion between the coating materials is strong, the overall strength of the diaphragm coated with the nanofiber coating of the same thickness is increased by 2-10% compared with the strength of the non-nanofiber coating diaphragm. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] The present invention first provides a polymer nanofiber formed particle, the preparation steps of which are as follows:
[0040] First, one or more polymer nanofibers are prepared into a dispersion, wherein the polymer nanofiber raw material can be a granular or pre-dispersed liquid raw material (most of the polymer nanofibers themselves exist in the form of a dispersion), and the polymer nanofiber is selected from any one or more of cellulose nanofiber whiskers (CNC), cellulose nanofibers (CNF), aramid nanofibers, PI nanofibers, PAN nanofibers, PAM nanofibers, and PVDF nanofibers; a solvent is added to prepare a dispersion of a certain concentration, and its viscosity is adjusted by the concentration; preferably, the viscosity of the prepared dispersion is less than 500cp, and deionized water is preferably selected as the solvent, and other solvents are replaced with deionized water as much as possible before use;
[0041] Then stir at a speed of 1000-1200r / min, and then use a homogenizer to high-speed shear the dispersion at a speed of 12000rpm to open the intermolecular force to form a well-flowing uniform mixed liquid, followed by low-temperature drying at 60-90°C, preferably 60-70°C. Low-temperature drying can minimize the aggregation of nanofibers during the drying process, maintain the stability of the structural state as much as possible, and is conducive to the next step of crystallization to improve consistency.
[0042] Finally, the polymer nanofiber forming particles are obtained by heating, crystallizing, crushing, screening and demagnetizing. The heating temperature is set to be 10-40°C lower than the melting point of the polymer nanofiber material. The product obtained after the drying and curing is evenly spread in a heatable container and placed in an oven or muffle furnace at a certain temperature, preferably heated for 24 hours. The present invention sets the heating crystallization temperature to be 10-40°C lower than the melting point of the raw polymer nanofiber, so that the nanofiber is secondary crystallized to obtain secondary crystal particles of the polymer nanofiber. The heating at this temperature makes the distance between the lattices smaller, and the molecular arrangement becomes more compact. Then, through high-temperature crystallization, the nano whiskers form new crystals. The crystal morphology is controlled by strictly controlling the temperature parameters and adopting the method of slowly heating up and extending the holding time and cooling at a high speed. The new crystals formed by polymer nanofibers are crushed into original crystals (CNC cellulose particle size 4-10nm, aramid fiber particle size 40-60nm, PI fiber particle size 0.3-0.7um) or grains close to the original crystals. Various crushing methods such as grinding with a grinder, mortar grinding, and air flow crushing can be used. Then, the large particles that are not fully ground are removed through screening, and then the magnetic foreign matter that may enter the entire production process is removed through a demagnetization system, and finally uniform small-sized secondary solid particles are obtained.
[0043] Preferably, after the homogenization and emulsification, the emulsified product is subjected to vacuum freeze drying; preferably, the vacuum freeze drying includes: firstly, rapid freezing at a temperature of -50°C to -55°C to form solid ice, then vacuuming for 30 minutes to a pressure of 5-10Pa, and freeze drying for 18 hours in a vacuum environment. Vacuum freeze drying has an important influence on maintaining the stability of the polymer nanofiber structure. In the freeze drying process, the solid ice is directly sublimated into water vapor and processed by the condenser. This process ensures the stability of the polymer nanofiber structure, prevents the aggregation of nano molecules, and loses the nano size effect.
[0044] Preferably, in order to further optimize the product performance, inorganic nanopowders can also be added to the dispersion under stirring conditions and stirred for 60 minutes; the inorganic nanopowders include α-phase alumina, γ-phase alumina, β-phase alumina, mixed-phase alumina, boehmite, silicon oxide, zirconium oxide, magnesium hydroxide, aluminum hydroxide, aluminum titanate, barium titanate, lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum titanium oxide, sulfide electrolyte powder, lithium iron phosphate, lithium iron manganese phosphate, NCA ternary positive electrode, NCM ternary positive electrode, nano silicon, micron silicon, silicon-containing negative electrode material, silicon-carbon negative electrode material, any one or more; the particle size is 1nm-5000nm; preferably 10nm-2000nm, the smaller the particle size of the inorganic powder, the smaller the coating thickness that can be made in later applications.
[0045] The polymer nanofiber shaped particles provided by the present invention are prepared by the above-mentioned preparation method.
[0046] The present invention also provides a lithium battery separator coating slurry, and the preparation method thereof is as follows:
[0047] S1: mixing the polymer nanofiber forming particles, an aqueous dispersant and pure water to obtain a dispersion slurry, wherein the mass percentages of the polymer nanofiber forming particles, the aqueous dispersant and the pure water in the dispersion slurry are 5%-50%, 0.5%-5% and 50%-95% respectively;
[0048] The aqueous dispersant is selected from one or more of polycarboxylic acid ammonium salt, polycarboxylic acid sodium salt, polyacrylate, and phosphate ester;
[0049] S2: uniformly mixing the dispersed slurry obtained in S1 with an aqueous solution of an anti-settling agent, grinding, and obtaining a grinding slurry, wherein the mass percentage of the dispersed slurry in the grinding slurry is 10%-100%; the anti-settling agent is selected from one or more of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, cellulose, PVP, a block copolymer of polyurethane, a polyacrylate copolymer, and polyvinyl pyrrolidone;
[0050] S3: mixing the grinding slurry obtained in S2, a binder and a wetting agent to obtain the lithium battery separator coating slurry; the binder is selected from one or more of an emulsion-type acrylate-based polymer, a solution-type acrylate-based polymer, a polyurethane polymer, a polyacrylamide polymer, a polyimide polymer, and a polyamide polymer; the wetting agent is selected from one or more of an organosilicon-modified wetting agent, a polyether wetting agent, an acetylene alcohol wetting agent, and an alcohol wetting agent;
[0051] The mass percentage of the grinding slurry in the coating slurry is 80%-97%, the mass percentage of the adhesive is 3%-20%, and the mass percentage of the wetting agent is 0.05%-4%.
[0052] Preferably, the dispersed slurry can also be hydrophobically modified. In the step S2, a hydrophobic agent is added before grinding and mixed evenly before the subsequent steps are performed; further preferably, the hydrophobic agent accounts for 1-10% of the mass percentage of the grinding slurry. The hydrophobic agent can make the surface of the product have a strong hydrophobic, water-repellent and waterproof effect. The hydrophobic agent is selected from one or more of polysiloxane solution, paraffin material emulsion, fatty acid and its derivatives, fluorocarbon polymer, silane coupling agent, silicone resin, polymer emulsion or aqueous solution containing hydrophobic groups.
[0053] The present invention also provides an implementation method that can realize that the lithium battery separator coating slurry provided by the present invention is contained in any coating layer of the composite separator, and the specific steps are: coating the lithium battery separator coating slurry on the substrate separator, and then drying and winding to obtain the lithium battery separator; wherein the substrate separator includes a wet-process polyolefin porous membrane, a dry-process polyolefin porous membrane, a spinning composite porous membrane, a non-woven fabric porous membrane, etc.; the coating method is any one of micro-concave roller coating, anilox roller coating, spraying, slit coating, screw extrusion coating, etc.; during the drying process, the oven temperature range is 40-90°C.
[0054] Examples 1-10: The polymer nanofiber shaped particles provided by the present invention are prepared into lithium battery separator coating slurry according to the method provided by the present invention. Comparative Examples 1-3 are conventional coating slurry configurations of the prior art, as shown in Table 1 below:
[0055] Table 1 Lithium battery diaphragm coating slurry configuration table provided in the examples and comparative examples
[0056]
[0057] By comparing the pulping ingredients of different schemes in Table 1, it can be found that in Comparative Examples 1-3, polymer nanofiber dispersion or pulp is used as the main material for pulping. The dispersion or pulp itself has the problems of excessive viscosity and low polymer nanofiber solid content, which leads to the inability to make pulp and coat normally. The final pulp state is a gel aggregation state and cannot be coated. In addition, the solid content of the polymer nanofiber material is extremely low and the properties of the material itself cannot be exerted.
[0058] In Examples 1-10, different polymer nanofibers are selected to prepare molded particles, which become solid particles. Solid particles can effectively increase the usage of polymer nanofibers and give full play to the material advantages of the material itself. The apparent viscosity of the slurry used for coating is within 100cp, and can be used for coating normally.
[0059] A 5um wet-process polyethylene membrane was selected as the substrate membrane and set as control example 1; then the substrate membrane of control example 1 was coated with the coating slurries provided in the examples and comparative examples, respectively, wherein the corresponding slurries were directly coated on the substrate membranes in comparative examples 1 and 2, 20% alumina was also added in the coating of comparative example 3, and the slurries of examples 1 to 10 in the above table 1 were coated in examples 1 to 10. Then the performance of the composite membrane was tested, and the results are shown in the following table 2:
[0060] Table 2 Composite diaphragm performance test results
[0061]
[0062] As shown in Table 2, in Comparative Examples 1 and 2, pulp is used as the raw material for direct coating. Compared with Control Example 1, the coating has no obvious improvement on the diaphragm. Comparative Example 3 has a certain improvement on heat resistance due to the addition of alumina, but the improvement in heat resistance is mainly achieved through the manufacturing effect of alumina materials. The main factor limiting the full performance of nanofibers is the mass fraction of nanocellulose in the system. The mass fraction of nanofibers in Comparative Examples 1-3 cannot be improved, and the heat resistance of the diaphragm and the surface wettability of the electrolyte cannot be effectively improved. In addition, direct coating of nanofibers will penetrate into the pores of the substrate, causing a serious increase in air permeability and affecting the ionic conductivity of the diaphragm.
[0063] In Example 1-5, the microparticle units of the formed polymer nanofibers are configured into a slurry for coating. The viscosity of the coating slurry can be greatly reduced, and the solid content is greatly increased, which can give full play to the material advantages of the nanofibers. The coated film samples have obvious advantages over the comparative examples in terms of heat resistance and electrolyte wettability. The formed microparticle units can prevent the nanofibers from entering the pores of the base membrane and blocking the pores. The air permeability added value is significantly reduced, and the ion conductivity of the diaphragm is effectively improved. At the same time, the amount of polymer nanofiber material in the coating is increased, and the nanofibers between the units are linked by intermolecular forces such as hydrogen bonds. The hair fibers between the units are linked, and the units are nested with each other to form an interwoven network structure. The puncture strength of the diaphragm can be improved by the coating.
[0064] In Examples 6-10, different nanofibers are added with composite inorganic materials to form independent composite units. When coating the diaphragm, the inorganic materials are tightly connected together by the nanofibers between the composite units to form a complete grid-like coating. The thermal shrinkage is basically non-shrinking at 130°C / h. When the thermal shrinkage is 150°C / 0.5h, although the base film of the bottom layer has reached its melting temperature, the mesh structure of the coating enhances the rigid structure of the coating, which is sufficient to resist the force of the bottom diaphragm melting and shrinking. Therefore, the modified diaphragm can withstand 150°C / 0.5h, and the thermal shrinkage value is small. In addition, the overall puncture strength of the diaphragm is also effectively improved.
[0065] Because the polymer nanofiber forming microparticle unit coating forms an interwoven structure, and the melting point and temperature resistance of the polymer nanofiber itself are much higher than the ultra-high molecular weight polyethylene material of the substrate, when the temperature approaches or exceeds the melting point of polyethylene, the diaphragm loses its strength because the substrate softens or melts. The coating slurry coating of the present invention can also maintain a certain strength at a higher temperature and maintain the dimensional retention of the coating at a higher temperature. Therefore, the membrane rupture temperature of Examples 1-10 is much higher than that of Comparative Example 1 and Comparative Examples 1-3.
[0066] The base material of the diaphragm in the current market is a polyolefin porous membrane, and the coating is mainly divided into two categories: one is a heat-resistant coating based on inorganic materials; the other is a bonding coating based on PVDF materials. Among them, the heat-resistant coating has certain requirements for the overall thickness of the coating. Generally, a 3-4um ceramic coating can meet the requirement that the bidirectional dimension of the diaphragm heat shrinkage at 130℃ is ≤3%.
[0067] The polymer nanofiber material generally has a nanometer-scale diameter, and the diameter gradient is a few nanometers or more than ten nanometers. Therefore, this material has an extremely high specific surface area, which can bring more support sites to the substrate, and there are more binding sites between the materials, and the binding force is stronger. The thickness below 1um can be achieved, but it brings better heat resistance to the diaphragm. For conventional heat-resistant coatings, the coating is a discontinuous structure, which has no effect on the strength of the entire diaphragm at high temperatures. The coating slurry coating provided by the present invention has more binding sites, and its coating has a certain strength, which can improve the overall strength of the diaphragm. And under high temperature conditions, the strength of the polyolefin substrate diaphragm is lost as the temperature rises until there is no strength, and the nanofiber coating can maintain a certain strength, bringing a higher safety improvement to the diaphragm.
[0068] Secondly, because of the ultra-high specific surface area and affinity for electrolyte of the nanofiber coating, it can bring higher liquid absorption and retention capacity to the diaphragm, and bring higher charge and discharge rate performance.
[0069] There are currently two main ways to apply polymer nanofiber materials. One is to disperse them in an aqueous or oily solvent system, coat the substrate, and then dry the solvent to obtain a coating. The other is to dissolve the nanofibers in a solvent, coat the substrate, and then pass through a coagulation bath to form pores using a non-solvent-induced phase separation method. Both the first and second methods will cause a huge increase in the viscosity of the slurry when a small amount of material is added, making coating difficult. The first solution cannot form a uniformly spread coating due to the difficulty in dispersing the nanofiber material and the self-aggregation effect of the entire process. In particular, the second solution also requires the screening of solvents and non-solvents. The coating + phase separation process is extremely complex, and the coating equipment has low stability, which brings huge cost increases and process instability risks to the coated products.
[0070] The present invention subjects polymer nanofibers to secondary particle molding, and further compounds them with inorganic materials to form secondary molded particles with a core-shell structure. The coating slurry prepared with the secondary molded particles as raw materials has a low viscosity and can be coated using conventional aqueous diaphragm coating equipment and process schemes. The coating process is simple and controllable, so that the coated diaphragm has excellent heat resistance and liquid affinity and liquid retention capabilities.
[0071] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. A method for preparing polymer nanofiber shaped particles, characterized in that: The method comprises: preparing one or more polymer nanofibers into a dispersion, stirring at a speed of 1000-1200 r / min and then homogenizing and emulsifying, and then sequentially performing low-temperature drying, heating crystallization, crushing and screening, and demagnetization treatment to obtain the polymer nanofiber formed particles; The polymer nanofibers include any one or more of cellulose nanofiber whiskers (CNC), cellulose nanofibers (CNF), aramid nanofibers, PI nanofibers, PAN nanofibers, PAM nanofibers, PVDF nanofibers, PPS nanofibers, and PEEK nanofibers; The viscosity of the dispersion is less than 500 cp.
2. The preparation method according to claim 1, characterized in that: The temperature of the low temperature drying is 60-90°C; Preferably, the temperature of the low-temperature drying is 60-70°C.
3. The preparation method according to claim 1, characterized in that: The heating temperature is set to be 10-40° C. lower than the melting point of the polymer nanofiber material; Preferably, the heating time is 24 hours.
4. The preparation method according to claim 1, characterized in that: The preparation method further comprises: after the homogenization and emulsification, vacuum freeze-drying the emulsified product; Preferably, the vacuum freeze-drying comprises: firstly performing rapid freezing at a temperature of -50°C to -55°C to form solid ice, then evacuating to a pressure of 5-10Pa and maintaining the pressure for 18 hours.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The preparation method further comprises: adding inorganic nanopowder to the dispersion under stirring conditions, and continuously stirring for 60 minutes; Preferably, the inorganic nanopowder includes α-phase alumina, γ-phase alumina, β-phase alumina, mixed-phase alumina, boehmite, silicon oxide, zirconium oxide, magnesium hydroxide, aluminum hydroxide, aluminum titanate, barium titanate, lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum titanium oxide, sulfide electrolyte powder, lithium iron phosphate, lithium iron manganese phosphate, NCA ternary positive electrode, NCM ternary positive electrode, nano silicon, micron silicon, silicon-containing negative electrode material, silicon-carbon negative electrode material. Any one or more.
6. The preparation method according to claim 5, characterized in that: The particle size of the inorganic nanopowder is 1nm-5000nm; Preferably, the particle size of the inorganic nanopowder is 10nm-2000nm.
7. A polymer nanofiber shaped particle, characterized in that: The polymer nanofiber shaped particles are prepared by the preparation method described in any one of claims 1-6.
8. A lithium battery separator coating slurry, characterized in that: The preparation method thereof comprises: S1: mixing the polymer nanofiber forming particles obtained by the preparation method according to any one of claims 1 to 6, an aqueous dispersant and pure water to obtain a dispersion slurry, wherein the mass percentages of the polymer nanofiber forming particles, the aqueous dispersant and the pure water in the dispersion slurry are 5%-50%, 0.5%-5% and 50%-95% respectively; S2: uniformly mixing the dispersed slurry obtained in S1 with the anti-settling agent aqueous solution, grinding, and obtaining a grinding slurry, wherein the mass percentage of the dispersed slurry in the grinding slurry is 10%-100%; S3: mixing the grinding slurry obtained in S2, the binder and the wetting agent to obtain the lithium battery separator coating slurry; The mass percentage of the grinding slurry in the coating slurry is 80%-97%, the mass percentage of the adhesive is 3%-20%, and the mass percentage of the wetting agent is 0.05%-4%.
9. The lithium battery separator coating slurry according to claim 8, characterized in that: The dispersant is selected from one or more of polycarboxylic acid ammonium salt, polycarboxylic acid sodium salt, polyacrylate, and phosphate ester; The anti-settling agent is selected from one or more of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, cellulose, PVP, polyurethane block copolymers, polyacrylate copolymers, and polyvinyl pyrrolidone; The adhesive is selected from one or more of an emulsion-type acrylate-based polymer, a solution-type acrylate-based polymer, a polyurethane polymer, a polyacrylamide polymer, a polyimide polymer, and a polyamide polymer; The wetting agent is selected from one or more of an organosilicon-modified wetting agent, a polyether wetting agent, an acetylene alcohol wetting agent, and an alcohol wetting agent.
10. The lithium battery separator coating slurry according to claim 9, characterized in that: The preparation method also includes: hydrophobic modification of the dispersed slurry; The hydrophobic modification comprises: in the step S2, before grinding, a hydrophobic agent is added and mixed evenly, and then the subsequent steps are performed; Preferably, the mass percentage of the hydrophobic agent in the polishing slurry is 1-10%.